Retrospective Screening and Analysis of mcr-1 and blaNDM in Gram-Negative Bacteria in China, 2010–2019 - Fan, Rong; Li, Chuchu; Duan, Ran; Qin, Shuai; Liang, Junrong; Xiao, Meng; Lv, Dongyue; Jing, Huaiqi; Wang, Xin (Frontiers in Microbiology, 2020)
Currently, Gram-negative bacteria have developed multidrug and broad-spectrum drug resistance, and the numbers of species and strains carrying mcr or blaNDM genes are increasing. In this study, mcr-1 and blaNDM distribution of 12,858 Gram-negative bacteria isolated from wildlife, patients, livestock, poultry and environment in 14 provinces of China from 2010 to 2019 and the antibiotics resistance in regard to polymyxins (polymyxin B and colistin) and carbapenems of positive strains were investigated. A total of 70 strains of 10 species carried the mcr-1 gene, positive rates of patients, livestock and poultry, and environmental strains were 0.62% (36/5,828), 4.07% (29/712), 5.43% (5/92), respectively. Six strains of 3 species carrying the blaNDM gene all came from patients 0.10% (6/5,828). Two new mcr-1 gene variants (GenBank: MK965883, MK965884) were identified, one of which contains premature stop codon. The drug susceptibility results showed that all mcr-1 carriers were sensitive to carbapenems, among which, 66 strains were resistant and 4 were sensitive to polymyxins. The strains with the blaNDM gene had different degrees of resistance to carbapenems and were sensitive to polymyxins. The findings that species carrying mcr-1 or blaNDM genes were limited and mostly normal flora of opportunistic or low pathogenic organisms indicated that transfer of mcr-1 and blaNDM genes between bacteria was relatively limited in China. The none detection among wildlife compared with other sources supports the speculation that the emergence of and increase in polymyxins and carbapenem-resistant strains was mainly related to the selective pressure of antibiotics.